Enhancing Magnetic Communication between Metal Centres: The Role of s‐Tetrazine Based Radicals as Ligands. Issue 16 (15th January 2021) - Mavragani, Niki; Kitos, Alexandros A.; Brusso, Jaclyn L.; Murugesu, Muralee
Abstract: Although 1, 2, 4, 5‐tetrazines or s ‐tetrazines have been known in the literature for more than a century, their coordination chemistry has become increasingly popular in recent years due to their unique redox activity, multiple binding sites and their various applications. The electron‐poor character of the ring and stabilization of the radical anion through all four nitrogen atoms in their metal complexes provide new aspects in molecular magnetism towards the synthesis of new high performing Single Molecule Magnets (SMMs). The scope of this review is to examine the role of s ‐tetrazine radical ligands in transition metal and lanthanide based SMMs and provide a critical overview of the progress thus far in this field. As well, general synthetic routes and new insights for the preparation of s ‐tetrazines are discussed, along with their redox activity and applications in various fields. Concluding remarks along with the limitations and perspectives of these ligands are discussed. Abstract : Emerging s ‐tetrazine‐based materials demonstrate the vast applicability of these highly versatile systems. This contribution highlights their incorporation as tunable ligands in the development of molecule‐based magnets, where communication between paramagnetic centres is critical, thus opening new avenues in the design of high performing Single‐Molecule Magnets.